Law Enforcement Against the Use of Motorcycle Racing Mufflers in the City of Yogyakarta - Kelik Endro Suryono; Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Muffler that has a louder sound or racing exhaust. Replacing the muffler is a violation committed by the perpetrators, how is law enforcement against motorists using racing exhausts in the perspective of Law No. 22 of 2009 concerning Road Traffic and Transportation in the city of Yogyakarta and what obstacles are experienced. This research is a type of observational research (sociological juridical) by means of a field survey. The results of this research and discussion are that it is known that the process of law enforcement against vehicles that use racing exhausts through educational efforts on legal knowledge to the public, preventive efforts, namely prevention of violations of the law as well as obstacles and obstacles experienced by law enforcement officials is that there are officers not every time and every way who stand guard because of the limited number of members, the absence of special banners and signs regarding prohibitions and the low knowledge and awareness of the law by the community.